In-vivo modulation of thymus-derived lymphocytes with monoclonal antibodies in mice. I. Effect of anti-Thy-1 antibody on the tissue distribution of lymphocytes. - Le Gros, G S (1983)
A procedure is described for the in vivo removal of all detectable T lymphocytes from spleen and lymph nodes in mice. A single intraperitoneal injection of monoclonal anti-Thy-1 antibody into mice leads to rapid depletion of functional T cells from peripheral lymphoid organs, but not thymus. The extent of T-cell depletion is dependent on the cytotoxic titre of the anti-Thy-1 antibody used. Antibody with a median cytotoxic titre greater than 10(6) causes the complete removal of cells bearing Thy-1, Lyt-1 and Lyt-2 surface antigens from peripheral lymphoid populations in 3 days. Eight days after treatment Thy-1+, Lyt-1+ and Lyt-2+ cells begin to reappear in these organs. Splenic B cells, assayed by the expression of surface immunoglobulin (sIg) and by mitogenic responsiveness to bacterial lipopolysaccharide (LPS), are not affected by this treatment. The monoclonal anti-Thy-1 antibody does not appear to penetrate thymus tissue and bind to thymocytes. Anti-Thy-1 antibody, but not F(ab')2 is required for in-vivo T-cell depletion. These findings indicate that anti-Thy-1 antibody causes the removal of Thy-1+ cells from peripheral lymphoid tissue, and as the circulating levels of anti-Thy-1 antibody decrease, cells from the thymus repopulate the thymus-dependent areas of the depleted lymphoid organs.